Fractals de Rauzy - Messaoudi, A. (Elsevier B.V., 2005)
We study arithmetical and topological properties of a class of Rauzy Fractals. In particular, we give a parametrization of the boundaries of these sets and show that they are quasi-disks.
Rauzy fractals